2014
DOI: 10.1371/journal.pone.0104258
|View full text |Cite
|
Sign up to set email alerts
|

A Proteinaceous Fraction of Wheat Bran May Interfere in the Attachment of Enterotoxigenic E. Coli K88 (F4+) to Porcine Epithelial Cells

Abstract: Wheat bran (WB) from Triticum aestivum has many beneficial effects on human health. To the best of our knowledge, very little has been published about its ability to prevent pathogenic bacterial adhesion in the intestine. Here, a WB extract was fractionated using different strategies, and the obtained fractions were tested in different in vitro methodologies to evaluate their interference in the attachment of enterotoxigenic Escherichia coli (ETEC) K88 to intestinal porcine epithelial cells (IPEC-J2) with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Escherichia coli K88 is a typical kind of ETEC expressing K4 adhesin [ 20 ], which has been widely used to construct inflammation models in piglets [ 21 ], broilers [ 22 ], mice [ 23 ], epithelial cells [ 24 ], and macrophages [ 25 ]. Our previous studies identified that E. coli K88 treatment upregulated the expression of reactive oxygen species and inducible nitric oxide synthase in RAW264.7 cells [ 26 ], promoted the inflammatory response, and disrupted the intestinal barrier in mice [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli K88 is a typical kind of ETEC expressing K4 adhesin [ 20 ], which has been widely used to construct inflammation models in piglets [ 21 ], broilers [ 22 ], mice [ 23 ], epithelial cells [ 24 ], and macrophages [ 25 ]. Our previous studies identified that E. coli K88 treatment upregulated the expression of reactive oxygen species and inducible nitric oxide synthase in RAW264.7 cells [ 26 ], promoted the inflammatory response, and disrupted the intestinal barrier in mice [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that bacterial adhesion to the host cell surface is the initial step of pathogenesis, antiadhesive therapy provides a promising strategy to interfere with the interactions of microbes and toxins with host cells, inhibiting pathogenic colonization and infection . Various dietary components act as decoy receptors for pathogens and are considered safe to inhibit the development of multiresistant bacteria. , For example, peptide fractions from wheat bran and fermented soy bean extracts inhibited ETEC K88 binding to intestinal epithelial cells. Feed ingredients, including microbial exopolysaccharides and casein macropeptide released during cheese making, were reported to reduce ETEC binding to the intestinal mucosa of piglets. , These studies indicated the potential of food-derived glycoconjugates as antiadhesive substances and antimicrobial alternatives to prevent pathogenic colonization and infection.…”
Section: Introductionmentioning
confidence: 99%